Akkumulation reloaded: Wie Notenbanken und Staaten die Profite retten - Kader, Maria; Schwarzer, Uli (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2015)
Since the beginning of the financial crisis central banks are flooding the markets with money. Despite the wide use of unconventional monetary measures economic activity has not improved, esp. in the EU and signs of a worldwide recession are lurking. While the economic stimulus by monetary policy has been flawed by counteracting tendencies in the real economy (low profitability, private indebtedness) the measures taken had negative distributive consequences and might lead to an increase in inequality. Together with austerity measures by the state and its role as an insurance provider for capital anti-crisis policies have strengthened the position of wealthy income classes at the expense of low income classes.